Analisis Faktor-Faktor yang Mempengaruhi Penerimaan Pajak Daerah Di Kota Pontianak - Dwi Widyastuti, Reni (Program Studi Akuntansi Universitas Panca Bhakti, 2021)
This study analyzes the factors that influence Regional tax revenue in Pontianak City in 2009-2010 using the variables of population, Gross Regional Domestic Product (GRDP), inflation and number of industries. The purpose of this study was to determine how the effect of population, GRDP, inflation and number of industries on local tax revenues in Pontianak City in 2009-2010. The data used in this study are primary data for 2009-2010 sourced from the Central Statistics Agency (BPS) of Pontianak City and the Regional Finance Agency of Pontianak City. In this study using quantitative methods. The testing process used consisted of statistical testing including T test, F test and classical assumption testing including normality test, heteroscedasticity test, multicollinearity test. The results of data analysis with multiple regression showed that the population, GRDP and the number of industries had a positive and significant effect on local tax revenues, while inflation had no significant effect on Pontianak local tax revenues. Keywords: Regional Tax Revenue, Total Population, GRDP, Inflation and Number of Industries